Wood polymer composites and their contribution to cascading utilisation. (1st January 2016) - Teuber, Laura; Osburg, Victoria-Sophie; Toporowski, Waldemar; Militz, Holger; Krause, Andreas
Abstract: Due to a shortage of resources and a growing competition of land use, sustainable and efficient resource utilisation becomes increasingly important. The application and multiple, cascading utilisation of renewable resources is aimed at to ensure an allocation and future availability of resources. Wood polymer composites (WPCs) are a group of innovative materials consisting of mainly renewable resources. By means of summarizing recent research, it is shown how WPC can potentially contribute to an enhanced cascading utilisation. For the production of WPC, waste materials and by-products from wood and agricultural industry, e.g. offcuts, sawdust, residues from board manufacturing, pulping sludge, can serve as a raw material. Furthermore, the cited literature presents the use of recycled polymers and biopolymers as a potential alternative for the polymer component of WPC. By using biodegradable polymers, a fully biodegradable composite can be formed. In addition to using recycled materials and potentially being biodegradable, it is pointed out that WPC furthermore offers the possibility of being recycled itself, therefore being considered as a "green composite". Although the influence of contaminated waste streams and mixed filler and polymer types on the properties of WPC made with such recyclates is yet not fully understood and no collection systems exist for post-consumer WPC, in-house recycling on the production sites is identified as a promising option as it reduces production costs and enhances resource efficiency and cascading utilisation. On the basis of cited life cycle assessments, the eco friendliness of WPC is assessed resulting in the conclusion that WPC cannot compete with solid wood with respect to environmental impact but is an environmentally friendly alternative to neat plastics in several applications.